Synergistic phosphorized NiFeCo and MXene interaction inspired the formation of high-valence metal sites for efficient oxygen evolution. (20th April 2022) - Li, Ning; Han, Jingrui; Yao, Kaili; Han, Mei; Wang, Zumin; Liu, Yongchang; Liu, Lihua; Liang, Hongyan
Highlights: High-valence metal sites are formed via MXene coupling and phosphorization. In-situ Raman confirms the TMP are easily transferred into active species MOOH. DFT reveals the strong electronic interaction between TMP and MXene. NiFeCoP/MXene exhibits excellent OER performance ( η 10 : 240 mV). Abstract: Exploring low-cost, high-performance, and stable electrocatalysts toward the oxygen evolution reaction (OER) is highly desired but remains challenging. Transition metal hydroxide has been wildly utilized as a promising candidate, but practical implementation is impeded by insufficient catalytic activity, easy agglomeration, and poor conductivity. Here, we report that both phosphorization and combination with MXnene can improve the catalysts' intrinsic activity and conductivity. Besides, MXene also prevents the agglomeration of the nanoparticles, resulting in the enhanced exposure of active sites. Experimental characterizing and density functional theory simulations revealed that P species can attract electrons to promote the formation of high-valence states of adjacent metal atoms, and coupling MXene support can effectively modulate the electronic structure and optimize the d -band center, which boosts the OER performance. Consequently, the optimized NiFeCoP/Mxene catalyst exhibits a low overpotential of 240 mV at a current density of 10 mA cm −2, a small Tafel slope of 55 mV dec −1, and superior long-term stability of 40 h in 1 M KOH electrolyte, which is superior to other counterparts. Abstract : Image, graphical abstract .